Penggunaan E-Modul Interaktif Mata Kuliah Perkembangan Anak Berkebutuhan Khusus terhadap Peningkatan Motivasi Belajar Mahasiswa pada Kelas Inklusi - Dody Bakhtiar Al-Anshori; Sayidatul Maslahah; Eneng Bai Muinah; Rizki Siti Anugrah (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to analyze the use of interactive E-Modules in the course Development of Children with Special Needs and its effect on increasing student learning motivation in inclusive classrooms. The research employed a quantitative experimental method with a paired pretest-posttest group design. The subjects consisted of 40 students from the Special Education Department at Sultan Ageng Tirtayasa University. Data were collected through a learning motivation questionnaire and analyzed using the Shapiro-Wilk normality test and the Paired Sample T-Test. The results showed a significant increase in student learning motivation after the use of the E-Module, with a p-value < 0.05. The E-Module was inclusively designed using the principles of Universal Design for Learning (UDL) and multimedia technology, enabling appropriate access and learning interaction for all students. These findings indicate that the interactive E-Module is not only effective in enhancing learning motivation but also supports adaptive and inclusive learning in higher education.